2012
DOI: 10.1063/1.3684978
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale molecular dynamics study of jet breakup and ejecta production from shock-loaded copper with a hybrid method

Abstract: Ejecta production from the free surface of metals under shock loading is investigated using large-scale molecular dynamics (MD) simulations performed with a new (hybrid) method. A copper crystal, in contact with vacuum and with a sinusoidal surface finish representative of the roughness produced by a machine polishing, is divided in two zones, bulk and surface, calculated with, respectively, Hugoniostat and NVE ensembles. The bulk part is simulated using the Hugoniostat technique, which allows a very large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 46 publications
4
51
0
1
Order By: Relevance
“…As an example, in case where the defects are parallel grooves, Durand et al have recently used Molecular Dynamic (MD) simulations of large systems to show that the ejection process is as follows: (i) the ejected material forms sheets of liquid metal which go thinner and thinner; (ii) when sheets are sufficiently thin, holes appear and sheets break to form filaments; and (iii) those filaments stretch and finally break also to form spherical clusters. 1,4 It appears that the breaking of the sheets starts when the thickness is about several nanometers. So, to study the last parts of this phenomenon, microscopic simulations seem to be the good tool, and those MD simulations made possible to get the entire size distribution of the final spherical aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, in case where the defects are parallel grooves, Durand et al have recently used Molecular Dynamic (MD) simulations of large systems to show that the ejection process is as follows: (i) the ejected material forms sheets of liquid metal which go thinner and thinner; (ii) when sheets are sufficiently thin, holes appear and sheets break to form filaments; and (iii) those filaments stretch and finally break also to form spherical clusters. 1,4 It appears that the breaking of the sheets starts when the thickness is about several nanometers. So, to study the last parts of this phenomenon, microscopic simulations seem to be the good tool, and those MD simulations made possible to get the entire size distribution of the final spherical aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the classical hydrodynamics approaches suffer a lack of modeling and characterization of the rheological behavior of metals after shock loading; and data on surface tension and viscosity are needed. To our knowledge, only recent MD simulations performed on atomistic systems allowed to provide directly from computations ejecta size distributions [25][26][27]. Particulate…”
Section: Introductionmentioning
confidence: 99%
“…[25]. The analysis tools implemented for the characterization of the particles/aggregates/ejecta (these terms refer to the same thing) in size, velocity, position and mass are also described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades research on fragmentation mainly focused on the statistics of fragment masses (sizes) obtained by the breakup of heterogeneous materials [1,9,10]. A large number of experimental [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] and theoretical studies [13,[18][19][20][21][22][23][24] have confirmed that the mass distribution of fragments is described by a power law functional form. The exponent of the distribution was found to show a high degree of robustness, i.e., investigations revealed that the value of the exponent does not depend on the type of materials, amount of input energy, and on the way the energy is imparted to the system until materials of a high degree of heterogeneity are fragmented [1,9,10].…”
Section: Introductionmentioning
confidence: 99%